The Feasibility of Harvesting an Innervated Profunda Artery Perforator Flap for Breast Reconstruction. Issue 10 (October 2020) - Yano, Tomoyuki; Karakawa, Ryo; Yoshimatsu, Hidehiko; Fuse, Yuma; Shibata, Tomoyoshi; Kuramoto, Yukiko; Suesada, Nobuko; Miyashita, Hiroki
Abstract : Summary: The profunda artery perforator (PAP) flap has become an alternative option for breast reconstruction. Reliable perforators arise through the adductor magnus muscle, and dissection of the perforator is straightforward. Recently, we have found that the PAP flap with the sensory nerves can be harvested as an innervated flap. We discuss the feasibility of PAP flap neurotization. We reviewed 13 patients for whom innervated PAP flap harvesting was considered. The average age was 50.7 years. There are 3 different patterns of innervated PAP flap harvesting, Type 1: including a sensory nerve that can be found in the adipose tissue around the PAP flap, Type 2: including a sensory nerve that runs along the medial femoral circumflex system, and Type 3: including a sensory nerve that runs along the profunda artery perforators. The average flap harvest time was 2:11 ± 0:31, and a sensory nerve was identified in 10 of 13 cases (77%). No sensory nerves were found in the other 3 cases. The length of the included sensory nerve was 5.5 ± 1.6 mm on average. Types 1 and 2 were found in 3 patients (30%), Type 3 was found in 2 patients (20%), and combined Types 1 and 3, 2 and 3 were found in one patient each (10%). As sensory nerves run around the PAP flap or close to the perforators, it is easy to perform flap neurotization with the PAP flap. We believe that the PAP flap could be an alternative option to achieve sensate breast reconstruction.